The Politics of Recognition, Society, and Law: The Role of Muslim Society and the Kubu Raya Local Government in the Struggle of the Baha’is - Ali Akhbar Abaib Mas Rabbani Lubis; Sulaiman (Millah: Journal of Religious Studies, 2022)
This study discusses the politics of recognition of Baha'i adherents in Indonesia, who face obstacles in society. Apart from rejection in society, there are restrictions on their civil rights. This research was conducted in a regional locus in Kubu Raya, West Kalimantan.  In addition to discussing Baha'I adherents, who are not widely known by the public, especially in Kubu Raya, the study aims to provide important information regarding the relationship between the Baha’is and the majority Muslim community and the government of Kubu Raya. The research was conducted with a socio-legal approach, directly taking to the field by conducting interviews—data analysis through stages; data condensation, data exposure, conclusion, and verification. The research findings explain that Baha'i adherents have not been fully recognized by society and the law in Indonesia, but amid the Muslim majority community in Kubu Raya, they have never experienced rejection; in fact, their existence is very well received by the people of Kubu Raya who are known to be diverse and accept differences. Baha’i adherents are known to be very kind, friendly, and open by the people of Kubu Raya. On the other hand, the Baha'i adherents are not fully recognized by the Kubu Raya Local Government, so civil rights that should be fully guaranteed, assist-ed, and protected by the constitution, are still hampered because the existing system in government administration does not provide a Baha'i religion column.